Compatibility of intravitreally applied epidermal growth factor and amphiregulin - Bikbov, Mukharram; Khalimov, Timur A.; Cerrada-Gimenez, Marc; Ragauskas, Symantas; Kalesnykas, Giedrius; Jonas, Jost B. (International ophthalmology, 2021)
To examine the compatibility of intravitreally injected epidermal growth factor (EGF) and amphiregulin as EGF family member.